(3GdbjGOI h OhQgG aj GdYedjI GdGOGQjI (B/s - (3YHhj, RjO efjQs ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2007)
(3eONd Edi GdbjGOI , GdbjGOI GdEOGQjI , GJLGgGJ GdbjGOI h GdGOGQI , GdbjGOI ebGHd GdGOGQI , GdbjGOI GdgQejI ebGHd GdNGOejI , GdbGFO h UfGYI GdbQGQG h OhQg aj GOGQI GdGReGJ , HfjI GdbGFO(B.s
(3eQGLY U(B.187s
Keywords: (3EOGQI GdGYeGds; (3EOGQI GdGaQGOs; (3GdGOGQI GdYGeIs; (3GdbjGOIs